Perceptual Grouping Affects Haptic Enumeration Over the Fingers. (January 2016) - Overvliet, Krista E.; Plaisier, Myrthe A.
Spatial arrangement is known to influence enumeration times in vision. In haptic enumeration, it has been shown that dividing the total number of items over the two hands can speed up enumeration. Here we investigated how spatial arrangement of items and non-items presented to the individual fingers impacts enumeration times. More specifically, we tested whether grouping by proximity facilitates haptic serial enumeration (counting). Participants were asked to report the number of tangible items, amongst non-items, presented to the finger pads of both hands. In the first experiment, we divided the tangible items in one, two, or three groups that were defined by proximity (i.e., one nonitem in between two groups) and found that number of groups and not number of items were the critical factor in enumeration times. In a second experiment, we found that this grouping even takes place when groups extend across fingers of both hands. These results suggest that grouping by proximity affects haptic serial enumeration and that this grouping takes place on a spatial level possibly in addition to the somatotopic level. Our results support the idea that grouping by proximity, a principle introduced in vision, also greatly affects haptic processing of spatial information.